The Business Cycle and the Credit Cycle in Poland during the years 1998-2013 - Barczyk, Ryszard (Studia Oeconomica Posnaniensia, 2015)
Apart from general economic cycles, market economies are characterized by other specific cycles, which also include credit cycles. Fluctuations, whose sequence over time creates credit cycles, are absolute and/or relative changes in credit-related activities by banks, manifested in the form of oscillations in the bank loans granted for investment or consumption purposes. The aim of this article is to analyse the influence of general business cycles on changes in the credit activity of commercial banks and the reflexive relation between business activities and credit cycles. The paper consists of two parts. The first one presents the theoretical hypotheses formulated for the correlations analysed. The second part contains the results of an empirical analysis of the correlation coefficients for the studied variables, taking into account the time factor.